Produksi IgY Antivirus Avian Influenza H5N1 dan Prospek Pemanfaatannya dalam Pengebalan Pasif - Teguh Wibawan, I Wayan; Murtini, Sri; Damajanti Soejoedono, Retno; Kade Mahardika, I Gusti Ngurah (Jurnal Veteriner; Vol 10 No 3 (2009), 2009)
Immunoglobulin Y (IgY) in yolk has been shown in several studies to prevent both bacterial and viralinfections. This research was conducted to find evidence that IgY specific against avian influenza virus(AIV) of H5N1 subtype can be produced in a large quantity in egg yolk. Laying hens were vaccinated withAI killed-vaccine (IPB-Shigeta). The IgY was purified using affinity chromatograpy technique, and anti-H5activity was measured using a standard haemaglutination inhibition (HI) and agar gel immunodifusion.The concentration of IgY was calculated, and the protein pattern was detected using polyacrilamid gel(AGID) electrophoresis (PAGE). Anti H5 antibody as high as 27 – 29 HI units was detected and produce aspecific line of precipitation in AGID. The concentration of IgY was 7.89 mg/ml. Purified specific IgY consistof 6 main protein bands with molecular weights ranging from 35 to 225 kD. These proteins were sensitiveto heat treatment (75oC for 30 minutes), to acid condition (pH2) as well as the pepsin and trypsin. Theseresults indicated the possibility of using specific IgY for passive immunisation to prevent AIV infection oras immunotherapeutic applications for AI treatment in humans.
Keywords: Passive immunisation, avian influenza virus of subtype H5N1, specific IgY Egg Yolk